Internal Control as a Bridge to Superior Performance of the West Papua Provincial Government: Perspectives of Human Resources, Accountability, and Transparency - D. Resi, Yohanes; Mattalatta, Mattalatta; Maddatuang, Bachtiar; Soemaryo, Partono (Green Publisher Indonesia, 2025)
This study aims to analyze Internal Control as a bridge to the superior performance of the West Papua Provincial Government, by examining the influence of HR perspectives, accountability and transparency . This study uses a quantitative approach. The population of this study was 351 employees of the West Papua Provincial Secretariat, with a sample of 203 respondents, using the opinion of Hair et al, 2010 (7x29 indicators). The research data were obtained from the results of filling out the questionnaire and analyzed using SEM-AMOS. The results of the study show that (1) The quality of human resources, accountability and transparency have a positive and significant effect on the internal control system; (2) The quality of human resources, accountability and transparency have a positive and significant effect on the performance of regional government agencies; (3); Internal control has a positive and significant effect on the performance of regional government agencies; (4) Internal control can significantly mediate the effect of the quality of human resources, accountability and transparency on the performance of regional government agencies